Sacrifice imagined: violence, atonement, and the sacred - Hedley, Douglas (Continuum, 2011)
Sacrifice Imagined is an original exploration of the idea of sacrifice by one of the world's preeminent philosophers of religion. Despisers of religion have poured scorn upon the idea of sacrifice as an index of the irrational and wicked in religious practice. Nor does its secularised form seem much more appealing. One need only think of the appalling cult of sacrifice in numerous totalitarian regimes of the twentieth century. Yet sacrifice remains a part of our cultural and intellectual imaginary'. Hedley proposes good reasons to think that issues of global conflict and the ecological crisis